A Healthy-Productive Dwelling Model Based On Optimizing Of Space - Bani Noor Muchamad; Naimatul Aufa; Ira Mentayani (Unika Soegijapranata Semarang, 2017)
ABSTRACT This research has a long-term aim to help the government’s program in alleviating poverty and creating a healthy environment. The aim will be achieved by an implementation and trial of existing Optimizing of Space based on occupancy profiles. The trial and implementation were performed by using modeling techniques, both 3D graphic model and mock up model. The modeling techniques were performed through a design experiment process in a laboratory. It was selected based on the characteristics of the low economic, education and knowledge capacities, and the low level of awareness of the society in the slum areas. The result of the research is a healthy and productive dwelling model for the occupants. This innovation of a healthy and productive dwelling model can be a frame of reference for a mass dwelling establishment or construction done by the government, private companies (CSR), or NGOs in order to upgrade the slum areas and alleviate poverty. Keywords: poverty; slum area; modeling. ABSTRAK Penelitian ini bertujuan jangka panjang untuk membantu program pemerintah dalam pengentasan kemiskinan sekaligus menciptakan permukiman dan lingkungan yang sehat dan berkelanjutan. Tujuan ini akan dicapai melalui pengimplementasian sekaligus pengujian Konsep Optimalisasi Ruang berbasis profil penghuni yang telah ada. Implementasi dan pengujian Konsep Optimalisasi Ruang dilakukan dengan menggunakan metode pemodelan, baik model 3D grafis maupun maket (mock up). Metode pemodelan dilaksanakan melalui proses eksperimentasi desain di laboratorium. Metode pemodelan dipilih berdasar karakteristik kemampuan ekonomi, pendidikan/pengetahuan, dan tingkat kesadaran masyarakat yang tinggal di kawasan permukiman kumuh yang masih rendah. Hasil penelitian adalah model hunian yang produktif dan sehat bagi penghuninya. Temuan inovasi model hunian produktif dan sehat ini dapat dijadikan acuan untuk pembangunan/pengadaan hunian massal yang dilaksanakan melalui program pemerintah, swasta (CSR), ataupun swadaya masyarakat untuk penataan permukiman kumuh dan pengentasan kemiskinan. Keywords: kemiskinan; permukiman kumuh; pemodelan